Case studies about urban management of gated communities in Chía-Colombia - Mendoza-Jaramillo, Alejandro (Prospectiva. Revista de Trabajo Social e Intervención Social, 2016)
This research selects two gated communities –GC– installed in Chia-Colombia in order to analyze through case studies, urban management –UM– that local government had front this individual urban phenomenon in comparative perspective of the 1990s and 2000. Thus, interested in knowing the convergences and divergences in the urban management, for which two gated communities were selected at the discretion of pairing cases –Condominio Santa Ana de Chia and Hacienda el Fontanar respectively– and three analytical dimensions: Physical and urban aspects, Social appropriation of project and Taxation and regulatory and institutional framework. The text ends with some reflections on the lessons that leaves the urban management conducted in both gated communities and proposed adjustments to improve existing instruments.